DIGITAL LEARNING ORGANIZATION: A BIBLIOMETRIC ANALYSIS (2000 - 2025) - Moider, Noor Arifah; Ariffin, Tengku Faekah Tengku; Nordin, Hasniza (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Digital learning organization (DLO) refers to the culture of knowledge through digital platforms to support continuous learning at the individual, team and organizational levels. In the wake of the rapid digitalization of artificial intelligence (AI) into education, students are widely immersed in the integration of digital technology. However, these digital challenges require teachers to engage in life-long learning, to navigate towards effectiveness in teachers’ job scope and to be more adaptable to the transformation in education. This article aims to examine a bibliometric analysis through a scientific data-based on DLO publications. The performance analysis and mapping analysis were employed in this study to provide a comprehensive picture in DLO research, in terms of the patterns of publication, collaboration and interconnection within the DLO field, to identify the trends, establish a strong foundation for literature development and to determine the research gaps in the existing knowledge. In addition, multifaceted indicators are examined through this bibliometric study, including trends, authors, countries and keywords. From the Scopus database (2000 – 2025), 200 scholarly publications were revealed. The results indicate that publications and citations have an increasing trend over the 25 years. This research can provide a foundation for future empirical studies to give a deeper understanding of DLO. By mapping this intellectual structure of DLO, this study enhances the conceptualization of DLO and the relationship between DLO and other constructs.